Obsessive-compulsive symptoms and related risk and protective factors in Black individuals in Canada - Dromer, Elisabeth; Jacob, Grace; Williams, Monnica T.; Moshirian Farahi, Seyed Mohammad Mahdi; Darius, Wina; Kogan, Cary Samuel; Cénat, Jude Mary (Frontiers in Psychology, 2025)
BackgroundData from the United States showed that Black individuals face unique issues related to obsessive-compulsive disorder (OCD). However, Canadian research on OCD among Black individuals remains very limited. The present study aims to document obsessive-compulsive (OC) symptoms and related risk and protective factors in Black individuals aged 15 to 40 years old in Canada.MethodsA total of 860 Black individuals (75.6% female) aged 15–40 years were recruited as part of the Black Community Mental Health in Canada (BcoMHealth) project. Independent t-tests, ANOVA, and multivariable linear regressions were used to assess OC symptom severity and identify risk and protective factors.ResultsBlack individuals presented high levels of OC symptoms. Results showed that Black individuals born in Canada experienced more OC symptoms compared to those born abroad. Results also showed that there were no differences between Black women, Black men, and those who identified their sex as “other.” Everyday discrimination, internalized racism, and microaggressions positively predicted OC symptoms, while social support negatively predicted OC symptoms.LimitationsLimitations of this study include its cross-sectional nature, which prevents us from establishing causal links, not assessing for the clinical diagnosis of OCD, and using self-report measures. Results support that different forms of racial discrimination contribute to the development and severity of OC symptoms in Black individuals in Canada. Social support may play a protective role for those individuals. These factors must be considered in future research and in the assessment and treatment of Black individuals with OCD.